Chemoprevention of Colon and Small Intestinal Tumorigenesis in APC(min/+) Mice by SHetA2 (NSC721689) without Toxicity - Benbrook, Doris Mangiaracina (2013)
The occurrence of intestinal polyps in people at high risk for developing colorectal cancer provides an opportunity to test the efficacy of chemoprevention agents. In this situation of treating otherwise healthy people, the potential for toxicity must be minimal. The small molecule flexible heteroarotinoid (Flex-Het), called SHetA2, has chemoprevention activity in organotypic cultures in vitro and lack of toxicity at doses capable of inhibiting xenograft tumor growth in vivo. The objective of this study was to evaluate SHetA2 chemoprevention activity and toxicity in the APC(Min/+) murine model. Oral administration of SHetA2 at 30 and 60 mg/kg five days per week for 12 weeks significantly reduced development of intestinal polyps by 40 to 60% depending on the dose and sex of the treatment group. Immunohistochemical and Western blot analysis of polyps demonstrated reduced levels of cyclin D1 and proliferating cell nuclear antigen (PCNA) in both SHetA2 treatment groups. Western blot analysis also demonstrated SHetA2 induction of E-cadherin, Bax and caspase 3 cleavage along with reduction in Bcl-2, cyclooxygenase-2 (COX-2) and vascular endothelial growth factor (VEGF), consistent with SHetA2 regulation of apoptosis, inflammation and angiogenesis. Neither dose caused weight loss nor gross toxicity in APC(Min/+) or wild type littermates. Magnetic resonance imaging (MRI) of cardiac function showed no evidence of SHetA2 toxicity. SHetA2 did not alter left ventricular wall thickness. In summary, SHetA2 exerts chemoprevention activity without overt or cardiac toxicity in the APC(Min/+) model. SHetA2 modulation of biomarkers in colon polyps identifies potential pharmacodynamic endpoints for SHetA2 clinical trials.